Sparing the Perineal Body: A Modification of the Posterior Sagittal Anorectoplasty for Anorectal Malformations with Rectovestibular Fistulae - Badillo, Andrea; Tiusaba, Laura; Jacobs, Shimon Eric; Al-Shamaileh, Tamador; Feng, Christina; Russell, Teresa Lynn; Bokova, Elizaveta; Sandler, Anthony; Levitt, Marc A. (European Journal of Pediatric Surgery, 2023)
Background The posterior sagittal anorectoplasty (PSARP) used to repair an anorectal malformation (ARM) with a rectovestibular fistula involves incising the perineal body skin and the sphincter muscles and a posterior sagittal incision to the coccyx. Perineal body dehiscence is the most common and morbid complication post-PSARP which can have a negative impact on future bowel control. With consideration of all the other approaches described to repair this anomaly, we developed a perineal body sparing modification of the standard PSARP technique.Methods Four patients with ARM with a rectovestibular fistula were repaired with a perineal body sparing modified PSARP at a single institution between 2020 and 2021. The incision used was limited, involving only the length of the anal sphincter, with no incision anterior or posterior to the planned anoplasty. Dissection of the distal rectum and fistula was performed without cutting the perineal body. Once the distal rectum was mobilized off the posterior vaginal wall and out of the vestibule, the perineal body muscles, where the fistula had been, were reinforced and an anoplasty was then performed.Results Operative time was the same as for a standard PSARP. There were no intraoperative or postoperative complications. No postoperative dilations were performed. All patients healed well with an excellent cosmetic result. All are too young to assess for bowel control.Conclusion We present a new technique, a modification of the traditional PSARP for rectovestibular fistula, which spares the perineal body. This approach could eliminate the potential complication of perineal body dehiscence.
Keywords: anorectal malformation; posterior sagittal anorectoplasty; rectovestibular